Analisis Kemampuan Siswa Kelas VIII dalam Menyelesaikan Soal Literasi Numerasi - Dekriati Ate; Yulius Keremata Lede (Mathematics Education Study Program, 2022)
In the 21st century, students are required to master the three skills, namely the quality of character, competence, and literacy. In order these skills to be achieved, the ability to think and reason is needed. One of literacy that closely related to the ability to thinks and reason is numeracy literacy. This research was conducted with the title: